PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IV-VII SD MENGGUNAKAN PROBLEM BASED LEARNING - Thiesya Futri Amanda Sy; Leksa Putri Nagara; Aulia Luthvia; Anggun; Dika Refani Saputri (STKIP Subang, 2026)
This study aims to determine the effect of implementing Problem Based Learning on elementary students’ mathematical problem-solving ability. The method used is a Systematic Literature Review (SLR) by examining ten relevant scientific articles published within the last ten years. The literature search was conducted through Google Scholar, ERIC, and Garuda (Garba Rujukan Digital) using keywords related to PBL and mathematical problem solving at the elementary level. Articles were selected based on inclusion and exclusion criteria, then extracted and synthesized using descriptive qualitative analysis. The review results show consistent findings that PBL has a positive and significant effect on students’ mathematical problem-solving ability. PBL effectively trains students across all stages of problem solving—understanding the problem, planning strategies, carrying out solutions, and evaluating results—through contextual problems, collaborative discussions, and independent inquiry. Several experimental studies report significantly higher achievement in classes using PBL compared to conventional learning, with some indicating contributions up to 43.4%. Variations of PBL supported by interactive media further strengthen outcomes, especially for HOTS-based problems and fraction topics. It is concluded that PBL is an effective, relevant, and recommended instructional model for improving elementary students’ mathematical problem-solving ability.